2012
DOI: 10.1111/j.1365-2745.2012.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape context and management regime structure plant diversity in grassland communities

Abstract: Summary1. Theoretical models show that environmental heterogeneity and dispersal are major determinants of species diversity at multiple scales, yet there are few studies from real landscapes that adequately integrate variation in the surrounding matrix. Understanding how landscape context and management influence species composition and diversity patterns across habitats and scales is an important goal in ecology with relevance for both management and conservation. 2. We used a system of 25 landscapes distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 57 publications
1
27
1
Order By: Relevance
“…The relationships of both plant and Orthoptera to landscape factors is in contrast to the findings of Marini et al (2008), who found no effect of landscape factors on plants, but a significant effect on Orthoptera. Generally, the findings in the literature regarding landscape effects on grassland plant communities are mixed, providing both evidence for (e.g., Söderström et al 2001;Ö ckinger et al 2012;Reitalu et al 2012;Schmucki et al 2012;JaniĆĄovĂĄ et al 2013) and against (e.g., Dauber et al 2003;Krauss et al 2004;Löbel et al 2006;Ö ster et al 2007;Jonason et al 2011). This may be a result of the overriding effects of local factors in some of the investigated grasslands (Dauber et al 2003;Marini et al 2008), which would not have been the case in the low-nutrient semi-natural grasslands in this study.…”
Section: Landscape Effectscontrasting
confidence: 48%
See 1 more Smart Citation
“…The relationships of both plant and Orthoptera to landscape factors is in contrast to the findings of Marini et al (2008), who found no effect of landscape factors on plants, but a significant effect on Orthoptera. Generally, the findings in the literature regarding landscape effects on grassland plant communities are mixed, providing both evidence for (e.g., Söderström et al 2001;Ö ckinger et al 2012;Reitalu et al 2012;Schmucki et al 2012;JaniĆĄovĂĄ et al 2013) and against (e.g., Dauber et al 2003;Krauss et al 2004;Löbel et al 2006;Ö ster et al 2007;Jonason et al 2011). This may be a result of the overriding effects of local factors in some of the investigated grasslands (Dauber et al 2003;Marini et al 2008), which would not have been the case in the low-nutrient semi-natural grasslands in this study.…”
Section: Landscape Effectscontrasting
confidence: 48%
“…The majority of these studies have focused on animal responses (Prevedello and Vieira 2010), however, an increasing number of studies have also shown responses in sessile organisms such as vascular plants (e.g., Ö ckinger et al 2012;Reitalu et al 2012;Schmucki et al 2012;JaniĆĄovĂĄ et al 2013). The properties of the surrounding landscape can significantly affect local species richness and composition in habitat patches through a number of mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…; Schmucki et al . ), support herbivore, pathogen or predator populations (Werling et al . ) or alter abiotic conditions through herbicide drift, pollution or temperature changes (Davis & Williams ; Marrs et al .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous studies (Steiner & Köhler, 2003;Schmucki et al, 2012;JaniĆĄovĂĄ et al, 2013), grassland species richness is affected by the surrounding landscape and mesic grasslands belong to the most affected communities due to their central position on the moisture and nutrient gradients and suitable habitat conditions for most of the generalist species. The results of this study emphasize the role of landuse history and landscape structure in shaping the composition and diversity of grassland ecosystems.…”
Section: Discussionmentioning
confidence: 71%